PENGARUH KOMUNIKASI INTERPERSONAL ORANG TUA -REMAJA (KETERBUKAAN DAN EMPATI) TERHADAP PRILAKU SEK PRANIKAH PADA REMAJA - Ratih, Rini Hariani; Yusmaharani, Yusmaharani; Nurmaliza, Nurmaliza (Jurnal Kebidanan Khatulistiwa, 2024)
Interpersonal communication or interpersonal communication is communication between people face to face, which allows each participant to capture other people's reactions directly, both verbally and non-verbally. Effective communication is communication that creates understanding, pleasure, influences attitudes, improves relationships and actions, so that any advice given by the mother or father is not considered a passing thought. This type of research is an analytical survey with a cross sectional design. The research was carried out at SMPN and MTSN in Tambang District with a population of 295 people and a sample of 192 people. sample of 192 people. The results of statistical tests show that the openness aspect (p=0.002) and the empathy aspect (p=0.001) are significant, so it can be concluded that there is an influence of the openness aspect and the empathy aspect on paramarital sexual behavior in adolescents.